MDGs 4 and 5 : Maternal and Child Health/Reproductive Health in LAC - Gordillo-Tobar, Amparo (World Bank, Washington, DC, 2013)
The Latin America and Caribbean (LAC) region fares well on achievement of the Millennium Development Goal (MDG) targets when compared with other regions, but the region has great disparities between and within countries on these goals. The region is also performing better than the rest of the developing world in relation to child mortality, having achieved more than 70 percent of the progress needed to reduce under-five mortality by two-thirds. However LAC still faces serious challenges regarding maternal mortality, achieving good public and individual health and alleviating poverty. For LAC, the MDGs are a historic opportunity to address all forms of inequality and attain the political will needed to achieve these goals.